2018
DOI: 10.1038/s41598-018-32509-9
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis of Campylobacter concisus respiratory genes provides insight into the pathogen’s growth requirements

Abstract: Campylobacter concisus is an emerging human pathogen found throughout the entire human oral-gastrointestinal tract. The ability of C. concisus to colonize diverse niches of the human body indicates the pathogen is metabolically versatile. C. concisus is able to grow under both anaerobic conditions and microaerophilic conditions. Hydrogen (H2) has been shown to enhance growth and may even be required. Analysis of several C. concisus genome sequences reveals the presence of two sets of genes encoding for distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 59 publications
(93 reference statements)
3
28
1
Order By: Relevance
“…Furthermore, C. concisus has the highest H 2 -uptake hydrogenase activity reported so far among pathogenic bacteria [167]. In agreement with these observations, H 2 was found to be needed for optimal growth under anaerobic conditions, and required for growth under microaerobic conditions, highlighting the importance of the H 2 -uptake hydrogenase in the pathogen's metabolism [76,168].…”
Section: Concisussupporting
confidence: 77%
“…Furthermore, C. concisus has the highest H 2 -uptake hydrogenase activity reported so far among pathogenic bacteria [167]. In agreement with these observations, H 2 was found to be needed for optimal growth under anaerobic conditions, and required for growth under microaerobic conditions, highlighting the importance of the H 2 -uptake hydrogenase in the pathogen's metabolism [76,168].…”
Section: Concisussupporting
confidence: 77%
“…Given this, supplementation of these amino acids and electron donors may potentially increase the growth of C. concisus and the effects of some of these substances on C. concisus growth were examined previously and in this study. H 2 gas has been demonstrated to be a highly effective electron donor for C. concisus growth [51,60]. It has been previously demonstrated that C. concisus had very low growth under anaerobic conditions and no growth under microaerobic conditions without H 2 [42].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of H 2 , C. concisus was able to grow under microaerobic conditions and the growth under anaerobic conditions greatly increased [42]. C. concisus has both a H 2 -uptake hydrogenase (Hyd) and a H 2 -generating hydrogenase (Hyf ) [51]. Site-directed mutagenesis demonstrated the critical role of H 2 oxidation for C. concisus growth, with C. concisus additionally found to exhibit extremely high H 2 -uptake hydrogenase activity [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations